PENDUGAAN MUTU BIJI KEDELAI BERDASARKAN SIFAT AKUSTIK PADA VARIASI TINGKAT KADAR AIR - Agustoria, Khairil; Andasuryani (Jurnal Teknologi Pertanian Andalas, 2025)
This study aims to estimate the quality of soybean seeds based on their acoustic properties at different moisture content levels as a rapid and non-destructive evaluation method. An experimental setup was developed using a sorting machine equipped with a microcontroller and an LM393 sound sensor to capture acoustic signals generated from the impact of soybean seeds on a reflector plate. The tested moisture contents were 10.65%, 13.65%, 16.65%, 19.65%, and 22.65%, in accordance with the SNI 01-3922-1995 standard. The results indicated that moisture content significantly affected the acoustic response of soybean seeds. As the moisture content increased, the detected acoustic voltage decreased. At the lowest moisture level (10.65%), the average amplitude was 3.617 mV, whereas at the highest moisture level (22.65%), it decreased to 3.135 mV. This reduction is attributed to the increase in seed elasticity (Modulus of Elasticity, MOE) caused by water absorption, which elevates the sound absorption coefficient and consequently reduces the propagation velocity of sound waves within the seeds. Statistical analysis confirmed that the differences in acoustic values among moisture levels were significant (P < 0.05). These findings suggest that acoustic properties can serve as an effective indicator for assessing soybean seed quality based on moisture content variation. Keywords: acoustics; amplitude; moisture content; soybean.